ІНТЕРАКТИВНЕ НАВЧАННЯ ЯК ЗАСІБ ФОРМУВАННЯ ЕМОЦІЙНОГО ІНТЕЛЕКТУ СТАРШОКЛАСНИКІВ (Pedagogy of Higher and Secondary Education, 2012)
У статті розкрито необхідність використання інтерактивного навчання у формуванні емоційного інтелекту старшокласників та розглядаються шляхи та методи вирішення проблеми формування емоційного інтелекту засобами інтерактивного навчання на уроках хімії та біології.Ключові слова: інтерактивне навчання, емоції, емоційний інтелект, поетапне формування, компонентний склад емоційного інтелекту.The article reveals the necessity of the usage of interactive learning while conditioning the emotional intelligence of the high school students. Some ways and methods of solving the problem of intelligence by means of interactive learning at the lessons of Chemistry and Biology are considered.Key words: interactive learning, emotions, emotional intelligence, step-by-step conditioning, the component of the emotional intelligence.
Keywords: interactive learning; emotions; emotional intelligence; step-by-step conditioning; the component of the emotional intelligence